Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Matematika Siswa - Ramadhani Putri, Hayati; Titi Solfitri; Maimunah (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2024)
This research was conducted to improve the learning outcomes of class VIII SMP S Beer Seba Pekanbaru students by utilizing the problem based learning (PBL) model. This research uses a classroom action research strategy based on Kemmis and Mc Taggart. There are two cycles and each cycles has 4 distinct phases in conducting this research: preparation, implementation, observation, and analysis. A total of seventeen eighth grade students (11 boys and 6 girls) from Beer Seba Middle School in Pekanbaru participated in this research. This research data was collected using test sheets given at the end of the cycle and teacher and student observation sheets given at the beginning of each session. Analyzing student learning outcome data and teacher and student activity data is the data analysis technique used. Analysis of research data shows that the learning process and mathematics learning outcomes have increased between the periods before and after the action. This can be seen from the increase in student completion rates and the increasingly aligned teacher and student activities with the plan for each session. In cycle I, 41.17% of students obtained basic KKM scores; in cycle II this figure increased to 64.7%; and in cycle III it increased again to 82.3%.